Interpretasi Dampak Keuangan Keluarga Tenaga Kerja Wanita (Studi Fenomenologi TKW Pamekasan yang Berimigrasi ke Saudi Arabia dan Malaysia) - Agus Sugiono; Aminatus Zakhra; Evi Malia (Faculty of Economics and Business Mulawarman University, 2017)
This research tries to reveal how far the financial impact of migrant workers who migrate to Saudi Arabia and Malaysia. The method used is qualitative / non positivistic method (Non Mainstream) through understanding method (verstehen) with Interpretive Paradigm and Husserl Transcendental Phenomenology approach. The main informants in this study as many as 6 people while the relevant institutions, researchers made a second informant to confirm data about TKW. This research reveals that the financial impacts of TKW Pamekasan families who immigrated to Saudi Arabia and Malaysia do exist, although they are not very significant, but in their view are significant because they bring a lot of changes to their lives, especially in the form of